Construction of a 9, 9′-bifluorenylidene-based small molecule acceptor materials by screening conformation, steric configuration and repeating unit number: a theoretical design and characterization. Issue 39 (2nd October 2017) - Sui, Ming-Yue; Geng, Yun; Sun, Guang-Yan; Wang, Jian-Ping
Abstract : The effects of molecular conformations, steric configurations and repeat units on the 99BF-based on photovoltaic properties were designed and compared at the molecular level. As a result, thep -conformational linear of the 4-unit molecule may be a high-performance 99′BF derivative. Abstract : The molecular geometry and spatial state determine the photoelectric properties, which are the main factors affecting the performance of devices in organic photovoltaics (OPVs). Designing and comparing the effects of molecular conformations, steric configurations, and repeating unit numbers on photovoltaic properties for a unitary unit at the molecular level is systematic and meaningful research. The density functional theory (DFT) and time dependent density functional theory (TDDFT) methods are used to calculate the electronic structure, the open circuit voltage ( V OC ) and key parameters closely relevant to the short-circuit current density ( J SC ), including the absorption spectrum, electron–hole correlation, driving force and interface charge separation ( k inter-CS ) and recombination rate ( k inter-CR ), as well as the LUMO orbital compositions of each fragment to explain the geometric-nature relationship and characterize the molecular photovoltaic performance. The results showed that thep conformational linear structure of the 4-unit molecule shows large V OC, easy exciton dissociation, matching energy levels and absorption spectra with the donor, and large k inter-CS and small k inter-CR at the donor/acceptor interface. Our conclusions indicate that systematic screening of molecular geometry and spatial state is an effective strategy for designing high-performance non-fullerene small molecule acceptors. Finally, we hope that our investigations in this study could provide theoretical assistance for further optimization of the acceptor materials for OPVs.